Root cause analysis for shunt reactor failure in 500 kV power system. (October 2019) - Arias Velásquez, Ricardo Manuel; Mejía Lara, Jennifer Vanessa
Abstract: Error has been long recognized as ubiquitous to the practice of electrical engineering for failure analysis, however, the correct methodology for decision science is necessary, especially with more statistical data analysis, in this research a new methodology proposal for update the international standard IEC 60076, by using the root cause analysis, with traditional methods, principal components analysis, data mining and causal map, it is possible to eliminate the error, in this analysis an update for the standards have been discovered, they need to improve to avoid critical failures in the power system, for the shunt reactors. This research explores the failure mode and root cause analysis of shunt reactors in high voltage through examination of the design and implementation in Latin American. The case study has been evaluated for a shunt reactor in the 500 kV power system, and a discussion is considered for 279 shunt reactors, they were located in Latin America, finally the principal component analysis, cluster and causal mapping for the strategy correction is done. In this research, a real case study has discovered with twelve failures modes and fourteen activities to avoid the design and construction mistakes, they should be considered to improve the international standards in the design of this important equipment for the power system. Furthermore, if in the analysis, the shunt reactor is full loading, all the fatigue fractures occur for a vibration in the shunt reactor with a partial discharge in the bushing connection and the spring closure of the equipotential devices. It results in a larger investigation with the new proposal, it is the root cause of one of the most critical points. These results indicated that re-evaluating shunt reactor design to ensure an optimal behavior with the components for this equipment in a full load stage. Highlights: A new methodology for shunt reactors root cause analysis. The results can be used for the update the IEC 60076–2011 for reactor design. The new proposal is verified with 279 shunt reactors and special failure analysis.